Momentum-resolved and correlation spectroscopy using quantum probes - Cosco F; Borrelli M; Plastina F; Maniscalco S (AMER PHYSICAL SOC, 2022)
We address some key conditions under which many-body lattice models, intended mainly as simulated condensed-matter systems, can be investigated via immersed, fully controllable quantum objects, namely quantum probes. First, we present a protocol that, for a certain class of many-body systems, allows for full momentum-resolved spectroscopy using one single probe. Furthermore, we demonstrate how one can extract the two-point correlations using two entangled probes. We apply our theoretical proposal to two well-known exactly solvable lattice models, a one-dimensional (1D) Kitaev chain and 2D superfluid Bose-Hubbard model, and show its accuracy as well as its robustness against external noise.